Role Of Visum Et Revertum And Provision In The Process Of Civil Action And Proposal Of Coveration (Study Resolution Number 50/Pid.Sus-Kids/2023/Pt Medan) - Gusria Amara; Risdalina Siregar; Indra Kumala Sari Munthe (Journal of Law, Politic and Humanities, 2024)
Proof is the most important thing in the judicial process, it is used to find the material truth that is the complete truth of a criminal case. In proof there are various means of proof such as testimony of witnesses, expert testimonies, letters, instructions, and indictments of the accused. In criminal acts of persecution, asylum, and murder, visum et repertum is often used as a means of proof in its proof. The study aims to identify and analyze the role of visum et repertum (ver) in the proof of a criminal offence under the Code of Criminal Procedure Law (KUHAP), and the function of visa et repertrum (ver), in the study of judgment No. 50/pid.sus-anak/2023/pt field). This research includes a type of normative jurisprudence that is supported by empirical research to obtain accurate or valid data. Based on the research carried out on the case study of judgment No. 50/PID.SUS-ANAK/2023/PT MEDAN) No.1267/ PID/B/2010/PN.JKT.BAR, it is a legal proof tool that has a connection to the judge in particular in decision-making. Nevertheless, the judge is free to judge the truth contained in the evidence of a letter issued by such an expert. Therefore, in deciding a matter, return to the judge himself, which is to be based on the reasoning and consideration of the law. Furthermore, as one of the means of proof referred to in article 184, paragraph (1) of the Covenant, the visa et repertum shall be the discretion of the judge and shall be used as a guideline or as a grip in delivering a sentence against the offender. For in the testimony of the expert, the testimony of the judiciary called Visum et repertum, so clearly described what really is the cause of a crime, whether it is persecution, serious injuries if resulting in death.